Echoing Events - van der Vlies, Tina (2022)
“Echoing Events” questions the perpetuation, actualization, and canonization of national narratives in English and Dutch history textbooks, wide-reaching media that tendentially inspire a sense of meaning, memory, and thus also identity. The longitudinal study begins in the 1920s, when the League of Nations launched several initiatives to reduce strong nationalistic visions in textbooks, and ends in the new millennium with the revival of national narratives in both countries. The analysis shows how and why textbook authors have narrated different histories – which vary in terms of context, epoch, and place – as ‘echoing events’ by using recurring plots and the same combinations of historical analogies. This innovative and original study thus investigates from a new angle the resistance of national narratives to change.